Uso de eletrodos a base de carbono impressos em 3D para a detecção eletroquímica de hidroxicloroquina em formulações farmacêuticas e em águas - Carvalho, Mayane Sousa (2023)
Although studies have demonstrated the inactivity of hydroxychloroquine (HCQ) towards SARS-CoV-2, this compound was one of the most prescribed by medical organizations for the treatment of hospitalized patients during the COVID-19 pandemic. As a result of it, HCQ has been considered as a potential emerging contaminant in aquatic environments. In this context, we propose a complete electrochemical device comprising cell and working electrode fabricated by the additive manufacture technology (3D-printing) for HCQ monitoring. For this, a 3D-printed working electrode made of a conductive PLA containing carbon black assembled in a 3D-printed cell was associated with square wave voltammetry (SWV) for the fast and sensitive determination of HCQ. After a simple surface activation procedure, the proposed 3D-printed sensor showed a linear response towards HCQ detection (0.4–7.5 μmol L-1) with a limit of detection of 0.04 μmol L-1 and precision of 2.4% (n =10). The applicability of this device was shown to the analysis of pharmaceutical and water samples. Recoveryvalues between 99 and 112% were achieved for tap water samples and, in addition, the obtained concentration values for pharmaceutical tablets agreed with the values obtained by spectrophotometry (UV region) at a 95% confidence level. The proposed device combined with portable instrumentation is promising for on-site HCQ detection.